HOW CAN BLOCKCHAIN REVOLUTIONIZE THE JORDANIAN BANKING SECTOR? - Saidat, Zaid (2022)
This article aims to explore blockchain, its applications, and its impact on banks in Jordan. The potential applications and improvements that blockchain might bring to the financial industry are astounding. Specifically, this study discussed the importance and possible areas of deploying blockchain technology in the banking sector of an emerging country with a fast-growing economy, namely Jordan, for different reasons. First, due to the shrinking interest-rate spread, Jordan's financial sector lacks long term lending and unsecured loans. Second, many economic revolutions, such as the internet and banking innovations, have impacted the Jordanian banking sector. As a result, the banking sector must undergo significant transformation to increase performance and attain new levels of growth. Third, the underlying technology in clearing payment and credit bank information systems could be revolutionized by blockchains. Fourth, blockchain applications facilitate "obtain credit, unsecured loans" scenarios, improving banking efficiency. Finally, while blockchain has much appeal because it allows free and self governing transfers, overall regulation and security for this decentralized system are still being created and agreed upon. We argue that for blockchain to change Jordan's financial system, legal frameworks must be in place to control banking transactions. This study explores the technology of blockchain, the emerging technology that powers Bitcoin and other cryptocurrencies. It highlights the features of the blockchain and shows why it could profoundly influence the entire banking sector in areas ranging from payments to settlements and identity services.